2019
DOI: 10.1101/768762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

StemBond hydrogels optimise the mechanical microenvironment for embryonic stem cells

Abstract: and kc370@cam.ac.uk 2 AUTHOR CONTRIBUTIONS KJC and JCRS designed the project. CCA and KJC developed the hydrogel technology. CL, CCA, BXT, MH, AW, CMV, and HTS performed the experiments and analysis. GGS analysed RNA sequencing data. WM performed the blastocyst injections. JCRS and KJC supervised ES cell experiments and analysis. PB supervised analysis of RNA sequencing data. KF supervised AFM analysis. CL and KJC wrote the paper. ACKNOWLEDGEMENTSWe are grateful to Peter Humphreys for assistance with imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(66 reference statements)
0
2
0
Order By: Relevance
“…107,110,112,113 The presence of specific ECM proteins facilitates tethering to biological or synthetic substrates and thereby facilitates efficient mechano-transduction of substrate stiffness to intracellular signals. 109,111,112,114 Oligodendrocyte precursor cells are multipotent cells responsible for regeneration in the central nervous system. It has recently been shown that age-dependent loss of function in oligodendrocyte precursor cells can be recapitulated by culture on stiff hydrogels which mimic the aged connective tissue and this loss of function can be restored on soft hydrogels which mimic young brains.…”
Section: Biocompatible Materials For Coculturementioning
confidence: 99%
“…107,110,112,113 The presence of specific ECM proteins facilitates tethering to biological or synthetic substrates and thereby facilitates efficient mechano-transduction of substrate stiffness to intracellular signals. 109,111,112,114 Oligodendrocyte precursor cells are multipotent cells responsible for regeneration in the central nervous system. It has recently been shown that age-dependent loss of function in oligodendrocyte precursor cells can be recapitulated by culture on stiff hydrogels which mimic the aged connective tissue and this loss of function can be restored on soft hydrogels which mimic young brains.…”
Section: Biocompatible Materials For Coculturementioning
confidence: 99%
“…Indeed, cells reside in native tissues in a complex microenvironment that guides and regulates their functions [2] . For instance, numerous studies have shown that the mechanical stiffness of the cellular microenvironment has a fundamental effect on cell migration [3] , stem cell differentiation [4] and can impact tissue regeneration [5] . Recently, evidence is rising that the geometrical properties of the cell's microenvironment also play an important role in the regulation of cellular functions, such as the intestinal crypt-villus architecture where dividing stem cells reside exclusively in the concave zone [6] .…”
Section: Introductionmentioning
confidence: 99%